1979
DOI: 10.1021/jm00187a014
|View full text |Cite
|
Sign up to set email alerts
|

Studies on analgesic agents. 1. Preparation of 1,2-diphenyl-2-(4-substituted 1-piperazinyl)ethanol derivatives and structure-activity relationships

Abstract: The preparation and analgesic activity of a series of the title compounds (8-55 and 57) are described. The intermediates, 2-phenyl-2-(1-piperazinyl)acetophenones 5 and 6, were prepared from benzyl phenyl ketones 3 via their bromides 4. On reduction, compounds 5 afforded the titled compounds 8-12, 16, and 26-48. Compounds 13-15 and 17-25 were obtained by alkylation or benzylation of 1.2-diphenyl-2-(1-piperazinyl)ethanols 7 derived from 6 by reduction. The reduction of 5 and 6 with metal hydrides predominantly g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Extensive NMR analysis showed that the product obtained was a structural isomer of diphenpipenol (the difference lies in the position of the hydroxyl group, Figure 1). This isomer has up to now only been mentioned once in literature (14), and no information on the potency of this compound has been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive NMR analysis showed that the product obtained was a structural isomer of diphenpipenol (the difference lies in the position of the hydroxyl group, Figure 1). This isomer has up to now only been mentioned once in literature (14), and no information on the potency of this compound has been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…The product 5 was hydrolyzed under acidic conditions to 2‐phenyl[1‐ 14 C]acetic acid 6 . By reaction between methyl phenyl sulfide 7 and 6 in the presence of phosphoric acid and trifluoroacetic anhydride produced compound 1‐(4‐(methylthio)phenyl)‐2‐phenyl[1‐ 14 C]ethanone 8 . Compound 8 was treated with bromine in acetic acid as solvent to give 2‐bromo‐1‐(4‐(methylthio)phenyl)‐2‐phenyl[1‐ 14 C]ethanone 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 3a-e were subjected to bromination using liquid bromine in chloroform to obtain a-bromo-1, 2-(p-substituted)diaryl-1-ethanones 4a-e as shown in Scheme 1 (Veeramaneni et al, 2003;Shimokawa et al, 1979).…”
Section: Chemistrymentioning
confidence: 99%